Quality over Quantity of Attention! Towards a Qualitative Attention‐Based View - Seidl, David; Splitter, Violetta; Whittington, Richard (Journal of Management Studies, 2026)
Abstract This Point proposes an ontological reorientation of the Attention‐Based View from a focus on attention quantity to attention quality – that is, from a quantitative to a qualitative Attention‐Based View. This shift is motivated by developments in both academic research and contemporary management. Drawing on practice theory, we reconceptualize attention not as a resource to be allocated and rationed, but as a set of sociomaterial practices of attending. We identify five constitutive qualities of these attentional practices: sociality, discourse, embodiment, materiality, and historicity. This conceptual shift moves beyond viewing attention as a limited and homogeneous resource, instead framing attending as a crescive and differentiated set of practices. We argue that this qualitative Attention‐Based View offers a deeper understanding of attention, one particularly relevant to contemporary strategizing and organizing.